Community empowerment program to increase individual empowerment of cadres in stunting prevention - Setyoadi Setyoadi; Annisa Wuri Kartika; Yati Sri Hayati; Cici Indah Setiowati (Universitas Aisyah Pringsewu, 2023)
The stunting management program must be carried out by multi-sectoral collaboration and involving community engagement. Individual empowerment of cadres can improve program outcomes. This study aimed to analyze the individual empowerment of cadres in community empowerment programs to overcome stunting. This study used quasi-experimental study with 40 respondents that selected by purposive sampling method. The data collection carried out by focus group discussion interview and individual community-related empowerment (ICRE) questionnaires. Statistics analysis using Paired t-test and 95% confidence intervals. The results of the analysis showed that all component in individual empowerment indicated that there was significant influence in empowerment program on improving individual empowerment cadre with p-value 0,000 in intention, participation, and critical awareness. Meanwhile the self-efficacy component obtained a p-value 0,001 and motivation 0,003. The results proves that the involvement of cadres in the stages of community empowerment can effectively improve community engagement and individual empowerment for the community health cadres. The provision of adequate training and supervision for health cadres is important in order to improve their role in community. Abstrak: Program penanggulangan stunting harus dilakukan dengan melibatkan kerjasama multisector dan keterlibatan masyarakat. Pemberdayaan kader secara individu dapat meningkatkan luaran dan keberhasilan program. Penelitian ini bertujuan untuk menganalisis tingkat pemberdayaan individu kader dalam program pemberdayaan masyarakat untuk mengatasi stunting. Penelitian ini menggunakan penelitian quasy-experimental dengan 40 responden yang dipilih dengan metode purposive sampling. Pengumpulan data dilakukan dengan wawancara focus group discussion dan kuesioner individual community-related empowerment (ICRE). Analisis statistik menggunakan Paired t-test dengan interval kepercayaan 95%. Hasil analisis menunjukkan bahwa semua setelah mengikuti program pemberdayaan masyarakat, terdapat pengaruh yang signifikan terhadap peningkatan semua komponen pemberdayaan individu dengan p-value 0,000 pada intensi, partisipasi, dan kesadaran kritis. Sedangkan komponen self-efficacy diperoleh p-value 0,001 dan motivasi 0,003. Hasil penelitian membuktikan bahwa keterlibatan kader dalam tahapan pemberdayaan masyarakat dapat secara efektif meningkatkan keterlibatan masyarakat dan pemberdayaan individu bagi kader kesehatan masyarakat. Pemberian pelatihan dan pengawasan yang memadai bagi kader kesehatan penting untuk meningkatkan peran mereka di masyarakat